Temporal of reef fish communities in the coastal water of Krueng Raya, Aceh Besar Regency, Indonesia - Maria Ulfah; Siti N. Fajri; Muhammad Nasir; Sri Agustina; Syahrul Purnawan (Aceh Journal of Animal Science, 2020)
Krueng Raya waters have a big potency on coral reef fish; However, there was no study was conducted to document this biodiversity. This data are crucial for the conservation plan. Therefore, the objective of the study was to examine the community structure of reef fish in the Krueng Raya coastal waters, Mesjid Raya Subdistrict, Aceh Besar, Indonesia. The sampling was conducted from January 2014 to December  2016. The data were collected at three stations by the Visual Census method with a depth of 3-4 meters. The research found the average amount of reef fish was 1743 individuals that were consisted of 93 species and comprised of 26 families. The Families dominating were Pomacentridae, Acanthuridae, Chaetodontidae, and Labridae. The distribution level of reef fish individually was influenced by the environmental conditions of the coral reef ecosystem. The severe condition of the coral ecosystem in the Krueng Raya coastal waters was caused by two factors. Firstly, fishing activities of the locals and tourists who deliberately stepping on the coral colonies and using unfriendly tools to catch the fish (speargun). Another factor was the occurrence of coral bleaching in 2016, of which almost 80% of the coral ecosystem in the Krueng Raya coastal waters was exposed to this phenomenon (bleaching).Keywords: Reef Fish, Acanthurida,  Communities Structure, Krueng Raya